Evaluation of topside equatorial spread F spectra estimators using Monte Carlo simulations - Galindo, F. R. (2008)
Radar observations typically employ periodic pulses to study any target. This scheme allows a simple processing of the data but the results frequently shows range or frequency aliasing. In order to solve this problem Uppala and Sahr [1] introduced the aperiodic technique (AT) in the radio science community. The AT is based on transmitting pulses at non uniform intervals and allows to study moderately overspread targets. Some equatorial Spread F (ESF) echoes belong to this category, particularly those from the topside. Using this idea Jicamarca Radio Observatory (JRO) has done a couple of experiments to study ESF echoes. Chau et al [2] used the Fast Fourier Transform (FFT) to compute spectra from those experiments and developed some criteria to remove clutter due to the aperiodic sequence. A second scheme of work was introduced by Hysell et al [3] and this scheme uses a Bayesian method to compute the spectra. Continuing this line of research a Monte Carlo simulations of typical echoes from equatorial ionospheric irregularities as well as ground clutter has been done to evaluate different aperiodic pulsing and inversion techniques to estimate the spectra or its corresponding AutoCorrelation Function (ACF). Our main objective is the estimation of the moderately overspread topside equatorial spread F (ESF) spectra. The optimal spectra estimators combined with radar imaging techniques might represent the unique means to estimate the irregularity power and energy spectral density versus wavenumber from the ground.